Local development in the rural regions of Eastern Europe: Post-socialist paradoxes of economic and social entrepreneurship - Bruno Grancelli (Journal for East European Management Studies, 2011)
This paper aims to highlight some paradoxes of the agrarian transformation in Hungary and Poland and the ways they impinge on the working of private and cooperative farming.The first section reassesses the debate on the specificities of cooperative management in the light of the de-collectivization of agriculture. The second addresses continuities and changes in the symbiotic relationship between big coops and rural households within the two ongoing processes of Europeanization and economic globalization. The final section discusses the 'cooperative difference' and concludes with some analytical insights on who makes it both in coops and households. – – Das Ziel dieses Beitrags ist es, gewisse Paradoxa der landwirtschaftlichen Transformationen in Ungarn und Polen sowie deren Auswirkungen auf die private und kooperative Landwirtschaft aufzuzeigen. Der erste Teil beleuchtet noch einmal die Debatte über die Ausprägungen von kooperativem Management unter dem Einfluss der De-Kollektivierung der Landwirtschaft. Der zweite Teil behandelt Kontinuitäten und Veränderungen in der symbiotischen Beziehung zwischen großen Kooperativen und ländlichen Haushalten innerhalb der laufenden Prozesse der Europäisierung und der wirtschaftlichen Globalisierung. Der letzte Teil bespricht die 'cooperative difference' und schließt mit einigen analytischen Betrachtungen über die Zukunftsaussichten für Kooperative und Haushalte.
Keywords: 650; Cooperatives conversion; family farms; subsistence agriculture; rural development in CEE